نوازل المياه في بلاد المغرب من خلال معيار الونشريسي ( ق 7 – 9 ه 13 – 15 م ) - بن حامد بوزيد; نجاع عبد الحفيظ (University Of Eloued جامعة الوادي, 2024)
تناولنا في هذا البحث موضوع المياه في بلاد المغرب الإسلامي من خلال كتاب الونشريسي(المعيار)، ولقد حاولنا التسليط الضوء على أهم المشكلات المائية في بلاد المغرب الإسلامي خلال العصر الوسيط، فاعتمدنا على استقراء المسائل الفقهية الواردة في هذا الكتاب واستخراج المادة التاريخية منها المتعلقة بالمياه. كما عرضنا مصادر المياه ومنشئات نقلها وتخزينها في هذه الفترة بالإضافة الى الاستخدامات الاجتماعية للمياه والأنشطة الاقتصادية المرتبطة بها، وتطرقنا إلى جهود الفقهاء المغاربة في حل هذه المشكلات، المتعلقة أساسا بملكية الماء والتزود به أحيانا أو تنظيم استخدام الماء العام وأولياته أحيانا أخرى، كما عرفنا بجهود سكان بلاد المغرب الإسلامي في التكيف مع مختلف الصعوبات التي واجهتهم في سبيل الحصول على الماء والاستفادة منه. In this research, we addressed the issue of water in the Islamic Maghreb through the book Al-Wansharisi (The Standard), and we tried to shed light on the most important water problems in the Islamic Maghreb during the Middle Ages. We relied on extrapolating the jurisprudential issues contained in this book and extracting historical material from it related to water. We also presented water sources and facilities for transporting and storing water during this period, in addition to the social uses of water and the economic activities associated with it, and we touched on the efforts of Moroccan jurists in solving these problems. Mainly related to the ownership of water and sometimes supplying it, or regulating the use of public water and its priorities at other times. We also learned of the efforts of the inhabitants of the Islamic Maghreb to adapt to the various difficulties they faced in obtaining water and benefiting from it.
مذكرة ماستر تاريخ تخصص تاريخ الغرب الإسلامي في العصر الوسيط
Keywords: الونشريسي; Aloncharisi; The Wansharisi; نوازل المياه; Cascades; Water calamities